Intelligent Virtual Agents 14th International Conference, IVA 2014, Boston, MA, USA, August 27-29, 2014. Proceedings - Bickmore, Timothy; Marsella, Stacy; Sidner, Candace; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the proceedings of the 14th International Conference on Intelligent Virtual Agents, IVA 2014, held in Boston, MA, USA, in August 2014. The 14 full and 24 short papers presented were carefully reviewed and selected from 78 submissions. In addition, the volume includes 25 demo and poster papers which were on display during the conference. The papers cover many aspects of intelligent virtual agent theory and application with a special focus on their use in healthcare.
Using Virtual Doppelgängers to Increase Personal Relevance of Health Risk Communication -- Luke, I am Your Father: Dealing with Out-of-Domain Requests by Using Movies Subtitles -- Animated Faces, Abstractions and Autism -- Is That How Everyone Really Feels? Emotional Contagion with Masking for Virtual Crowds -- Narrative Scenarios as a Testbed for Moral Agents -- On the Sociability of a Game-Playing Agent: A Software Framework and Empirical Study -- Effects of Coupling in Human-Virtual Agent Body Interaction -- Improving Motion Classifier Robustness by Estimating Output Confidence -- A Method to Evaluate Response Models -- When to Elicit Feedback in Dialogue: Towards a Model Based on the Information Needs of Speakers -- Representing Communicative Functions in SAIBA with a Unified Function Markup Language -- An Exploratory Analysis of ECA Characteristics -- Motion Parameterization and Adaptation Strategies for Virtual Therapists -- Corpus Creation and Perceptual Evaluation of Expressive Theatrical Gestures -- From Non-verbal Signals Sequence Mining to Bayesian Networks for Interpersonal Attitudes Expression -- ERiSA: Building Emotionally Realistic Social Game-Agents Companions -- Building Virtual Humans with Back Stories: Training Interpersonal Communication Skills in Medical Students -- Agents Behavior Semi-automatic Analysis through Their Comparison to Human Behavior Clustering -- Upper Body Animation Synthesis for a Laughing Character -- Simulating Deceptive Cues of Joy in Humanoid Robots -- Recommendations for Designing Maximally Effective and Persuasive Health Agents -- Recorded Speech, Virtual Environments, and the Effectiveness of Embodied Conversational Agents -- Exploring the Difference of the Impression on Human and Agent Listeners in Active Listening Dialog -- Planning Motions for Virtual Demonstrators -- With Us or Against Us: Simulated Social Touch by Virtual Agents in a Cooperative or Competitive Setting -- A Step towards Modelling Group Behaviour in Autonomous Synthetic Characters -- Dynamical Systems to Account for Turn-Taking in Spoken Interactions -- Virtual Reflexes -- Ascribed Gender and Characteristics of a Visually Androgynous Teachable Agent -- Full Body Interaction with Virtual Characters in an Interactive Storytelling Scenario -- Effects of an Agent s Displaying Self-adaptors during a Serious Conversation -- Let s Be Serious and Have a Laugh: Can Humor Support Cooperation with a Virtual Agent? -- Towards Realistic Female Avatar Creation: A Tool for Virtual Actor Design and Player Choice -- Metaphoric Gestures: Towards Grounded Mental Spaces -- From Data to Storytelling Agents -- Building Community and Commitment with a Virtual Coach in Mobile Wellness Programs -- Look on the Bright Side: A Model of Cognitive Change in Virtual Agents -- Naturalistic Pain Synthesis for Virtual Patients -- Generative Models of Cultural Decision Making for Virtual Agents Based on User s Reported Values -- Mapping Personality to the Appearance of Virtual Characters Using Interactive Genetic Algorithms -- Towards a Computational Architecture of Dyadic Rapport Management for Virtual Agents -- A Cognitive Model of Social Relations for Artificial Companions -- An Eye Tracking Evaluation of a Virtual Pediatric Patient Training System for Nurses -- Personalization and Personification: A Constructive Approach Based on Parametric Agents -- Interpersonal Attitude of a Speaking Agent in Simulated Group Conversations -- Birth Control, Drug Abuse, or Domestic Violence? What Health Risk Topics Are Women Willing to Discuss with a Virtual Agent? -- Evaluating the Impact of Anticipation on the Efficiency and Believability of Virtual Agents -- Developing Interactive Embodied Characters Using the Thalamus Framework: A Collaborative Approach -- The Right Agent for the Job? The Effects of Agent Visual Appearance on Task Domain -- Exploring Gender Biases with Virtual Patients for High Stakes Interpersonal Skills Training -- A Qualitative Evaluation of Behavior during Conflict with an Authoritative Virtual Human -- Steps towards a Challenging Teachable Agent -- Large-Scale Collection and Analysis of Personal Question-Answer Pairs for Conversational Agents -- Design Guidelines for a Virtual Coach for Post-Traumatic Stress Disorder Patients -- A Virtual Therapist for Speech and Language Therapy -- AsapRealizer 2.0: The Next Steps in Fluent Behavior Realization for ECAs -- A Data-Driven Method for Real-Time Character Animation in Human-Agent Interaction -- Compound Gesture Generation: A Model Based on Ideational Units -- Statistical Dialog Manager Design Tool for Health Screening and Assessments -- Towards Learning Nonverbal Identities from the Web: Automatically Identifying Visually Accentuated Words -- Maintaining Continuity in Longitudinal, Multi-method Health Interventions Using Virtual Agents: The Case of Breastfeeding Promotion -- Towards a Dyadic Computational Model of Rapport Management for Human-Virtual Agent Interaction -- Agent-User Concordance and Satisfaction with a Virtual Hospital Discharge Nurse.
Keywords: Computer science; Health informatics; User interfaces (Computer systems).; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; User Interfaces and Human Computer Interaction; Health Informatics; Electronic books